Degenerative Cervical Myelopathy induces sex-specific dysbiosis in mice - Farkas, Carlos; Retamal-Fredes, Eduardo; Ávila, Ariel; Fehlings, Michael G.; Vidal, Pia M. (Frontiers in Microbiology, 2023)
Degenerative cervical myelopathy (DCM) is the most common cause of spinal cord impairment in elderly populations. It describes a spectrum of disorders that cause progressive spinal cord compression, neurological impairment, loss of bladder and bowel functions, and gastrointestinal dysfunction. The gut microbiota has been recognized as an environmental factor that can modulate both the function of the central nervous system and the immune response through the microbiota-gut-brain axis. Changes in gut microbiota composition or microbiota-producing factors have been linked to the progression and development of several pathologies. However, little is known about the potential role of the gut microbiota in the pathobiology of DCM. Here, DCM was induced in C57BL/6 mice by implanting an aromatic polyether material underneath the C5-6 laminae. The extent of DCM-induced changes in microbiota composition was assessed by 16S rRNA sequencing of the fecal samples. The immune cell composition was assessed using flow cytometry. To date, several bacterial members have been identified using BLAST against the largest collection of metagenome-derived genomes from the mouse gut. In both, female and males DCM caused gut dysbiosis compared to the sham group. However, dysbiosis was more pronounced in males than in females, and several bacterial members of the families Lachnospiraceae and Muribaculaceae were significantly altered in the DCM group. These changes were also associated with altered microbe-derived metabolic changes in propionate-, butyrate-, and lactate-producing bacterial members. Our results demonstrate that DCM causes dynamic changes over time in the gut microbiota, reducing the abundance of butyrate-producing bacteria, and lactate-producing bacteria to a lesser extent. Genome-scale metabolic modelling using gapseq successfully identified pyruvate-to-butanoate and pyruvate-to-propionate reactions involving genes such as Buk and ACH1, respectively. These results provide a better understanding of the sex-specific molecular effects of changes in the gut microbiota on DCM pathobiology.